EFFORTS TO IMPROVE TEACHER COMPETENCE IN UTILIZING CANVA DIGITAL MEDIA IN LEARNING THROUGH IHT AT SDN SYEKH TUBAGUS ABDULLAH, TASIKMALAYA CITY - caswita, caswita; Noviyani, Selvi (Jurnal TEKNODIK, 2023)
Abstract: The problem in this research is the teacher's weakness in utilizing Canva-based learning media. Meanwhile, the aim of this research is to try to increase the teacher's competence in using Canva media for learning through In House Training (IHT). The research method used was a pre-experimental design with the type of one-group pre-test post-test design. It is said to be a pre-experimental design because this method is often referred to as "quasi-experimental". This design is not yet a real experiment. The results of the study show that based on the data obtained, it can be stated that in stage I the teacher at Syekh Tubagus Abdullah Elementary School can master the material for making Canva learning videos well. There is only one teacher whose score is below average. However, to further strengthen the teacher's skills in making animated learning videos, the author feels the need to re-do IHT phase II activities. Meanwhile in stage II the results of the IHT implementation were based on instruments filled in by 11 participants (teachers) and achieved an average score of 100, meaning that most of the indicators that had been set could be achieved very well. Based on the available data, it can be concluded that the In House Training (IHT) activity in the use of learning animation videos which was carried out for two days had a very extraordinary impact on the knowledge and skills of teachers as participants. During the In House Training (IHT) process, the participating teachers showed high enthusiasm and curiosity, so they were very motivated and enthusiastic to take part in the activity. In addition, new knowledge and skills needed to make animated videos for learning encourage participants to have a strong ability to be able to make their own animated videos.